Proposed upgrading work of Sultan Azlan Shah Airport terminal building for Malaysia Airport Holding Berhad at Jalan Lapangan Terbang 31350 Ipoh, Perak / Mohamed Asyraff Mohamed Redzuan - Mohamed Redzuan, Mohamed Asyraff (Faculty of Architecture, Planning and Surveying, 2011)
This final project of Interior Architecture is an assignment assign to a diploma student of interior architecture UiTm Perak Kampus Sri Iskandar. By going through this process,students will experience a lot of process and practical like a premilinary findings,analysis case study and synthesizing.Students will also master all aspect of interior design so that they can apply it for their preference in the future.The suggested title of this project is Proposed Upgrading Work at Sultan Azlan Shah Airport,lpoh( LTSAS). A lot of procedures and process have to be done before this report is complete.Every detail from every aspect have to be exact and compile together. This report must cover all aspect such as the layout plan,traffic flow inside the terminal and lot of other aspects. Sultan Azlan Shah Airport located at a very strategic location which is at Jalan Lapangan Terbang, about 6km from Ipoh city centre.As we all know an airport is like a gateway to the city it’s present.lt will give a first impression to a tourist that arrive at Ipoh.At this moment Sultan Azlan Shah Airport have only two destination flight which is Ipoh - Singapore and Singapore - The airliner company for this route is Firefly using an ATR 500 aircraft,this flight will fly 70 pax per flight.This airport usually receive about 240pax per day.But expected to increase in next year because a lot of new additional destinations.